Observations of AGN feeding and feedback on Nuclear, Galactic, and Extragalactic Scales. Issue Volume 15:Issue S359(2020) (March 2019) - Crenshaw, D. Michael; Gnilka, C. L.; Fischer, T. C.; Revalski, M.; Meena, B.; Martinez, F.; Polack, G E.; Machuca, C.; Dashtamirova, D.; Kraemer, S. B.; Schmitt, H. R.; Riffel, R. A.; et al.
Abstract: We investigate the processes of active galactic nuclei (AGN) feeding and feedback in the narrow line regions (NLRs) and host galaxies of nearby AGN through spatially resolved spectroscopy with the Gemini Near-Infrared Integral Field Spectrograph (NIFS) and the Hubble Space Telescope's Space Telescope Imaging Spectrograph (STIS). We examine the connection between nuclear and galactic inflows and outflows by adding long-slit spectra of the host galaxies from Apache Point Observatory. We demonstrate that nearby AGN can be fueled by a variety of mechanisms. We find that the NLR kinematics can often be explained by in situ ionization and radiative acceleration of ambient gas, often in the form of dusty molecular spirals that may be the fueling flow to the AGN.